2015
DOI: 10.4102/aej.v3i1.142
|View full text |Cite
|
Sign up to set email alerts
|

A review of the growth of monitoring and evaluation in South Africa: Monitoring and evaluation as a profession, an industry and a governance tool

Abstract: South Africa is one several African countries with an official ministry responsible for monitoring and evaluation (M&E). Some of the other countries include Ghana, Kenya, Benin and Uganda. The development of M&E in South Africa has been stymied in part by its interdisciplinary nature, trying to find roots within historically a very discipline-based higher education system. Over the last ten years, however, there has been a huge increase in the number, scope and quality of evaluations conducted in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…We assert that assessments of M&E systems in an African bureaucratic context need to consider both technical aspects and contextual factors related to the political and organisational environments within which the system is operating. This is in keeping with the emergent 'Made in Africa' themed research from regional evaluators at the African Evaluation Association (AfrEA), the South African Monitoring and Evaluation Association (SAMEA) and other relevant platforms (Abrahams 2015). While members of the M&E community in sub-Saharan Africa are increasingly arguing that there is something unique in the context of M&E in the region, the debate is only just emerging about how this context can best be taken into account through regionally relevant methods and approaches.…”
Section: Introductionsupporting
confidence: 63%
“…We assert that assessments of M&E systems in an African bureaucratic context need to consider both technical aspects and contextual factors related to the political and organisational environments within which the system is operating. This is in keeping with the emergent 'Made in Africa' themed research from regional evaluators at the African Evaluation Association (AfrEA), the South African Monitoring and Evaluation Association (SAMEA) and other relevant platforms (Abrahams 2015). While members of the M&E community in sub-Saharan Africa are increasingly arguing that there is something unique in the context of M&E in the region, the debate is only just emerging about how this context can best be taken into account through regionally relevant methods and approaches.…”
Section: Introductionsupporting
confidence: 63%
“…Mouton (2010) notes that, although programme evaluation was introduced into South Africa by international funding organisations, it was not until this practice was accepted and amalgamated in public service policy documents and frameworks that a culture of evaluation emerged. As such, using the NDP's concept of a developmental and capable state, the Department of Planning, Monitoring and Evaluation (DPME), as the organ of state responsible for the planning, monitoring and evaluation (Abrahams, 2015), endorses performance monitoring and evaluation as a key management intervention that should enhance public service capacity and increase the impact of service delivery interventions (DPME, 2014). A key initiative of the aforementioned department has been to introduce the outcomes approach which emphasises linking inputs and activities to outputs and outcomes (Phillips, 2012).…”
Section: Construct Definitionmentioning
confidence: 99%
“…Despite the importance of the aforementioned, few examples of successfully implemented evaluation studies could be found (Abrahams, 2015), especially in terms of training interventions. O'Malley, Perdue and Petracca (2013) note that many training interventions do not consistently provide evidence that links specific training efforts to desired outcomes, despite a commitment to training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario is mostly a result of the adoption of the New Public Management (NPM) approach to governance by many African governments which emphasizes results and the need for improving accountability and transparency. Evaluation has thus been viewed as a key performance management tool (Abrahams 2015;Mouton 2010). Further demand is now being driven by African evaluation practitioners advocating for the professionalization of evaluation.…”
Section: Introductionmentioning
confidence: 99%